The Relationship Between Primary Dysmenorrhea And Sleep Quality In Students Of The Faculty Of Medicine, University Of Nusa Cendana - Kelore, Imelda Martha Somi; Sihotang, Jojor; Folamauk, Conrad Liab H.; Manafe, Derri Tallo (Universitas Nusa Cendana, 2025)
When experiencing menstruation, it is often accompanied by pain which is commonly called dysmenorrhea. Primary dysmenorrhea experienced can cause discomfort both during activities and at rest so that it can affect sleep quality. The sleep quality of medical students is bad, apart from the lecture burden, it is suspected that it can also be influenced by the intensity of pain, such as when experiencing primary dysmenorrhea. To determine the relationship between primary dysmenorrhea and sleep quality in students of the Faculty of Medicine, University of Nusa Cendana. This research is an observational analytic study with a cross sectional design in students of the Faculty of Medicine, University of Nusa Cendana. Data was conducted by filling out the primary dysmenorrhea questionnaire and Pittsburgh Sleep Quality Index (PSQI) questionnaire by 106 respondents who met the inclusion criteria. Sampling was done by using stratified random sampling technique. The result was analyzed univariate and bivariate using Phi Correlation test. Data from 106 respondents showed that 63.2% of respondents experienced primary dysmenorrhea and as many as 36.8 respondents did not experience primary dysmenorrhea. For sleep quality, 80.2% of respondents had poor sleep quality and 19.8% of respondents had good sleep quality. In this study, it was found that more respondents had primary dysmenorrhea with poor sleep quality than good sleep quality. The results of the bivariate analysis with the Phi Correlation test showed the results of p value=0.520 (p> 0.05). There is no significant relationship between primary dysmenorrhea and sleep quality in students of the Faculty of Medicine, University of Nusa Cendana.